Monumentalizing the urban and concealing the rural/coastal A spatial reading of Matnog, Sorsogon, Philippines - Fe, Cecilia; L sta, Maria (Socio.hu Társadalomtudományi Szemle, 2016)
Abstract A discursive reading on how urban ideology is monumentalized, this article peels on the spatial experience of Matnog, Sorsogon as it transitions from a rural/coastal nature to the urban. Taking a spatial perspective, with theoretical underpinnings from Lefebvre’s concept of ‘oeuvre’, interlaced with Bourdieu’s take on social space and Giddens’ arguments on historical time, the article elaborates on the spatial machinations orchestrated to construct polemical spaces that deftly conceal spaces occupied by the poor. Extrapolating from photographs and maps of the place, field notes and interviews with Matnog residents who come from the low–income bracket, elucidated spatial consequences that weave discourses on the spatial problematic that unfolds through the shift in social space and historical time, consequential to the silencing of social differences in the transitioning spaces. Key words: rural and coastal area, urban, space transition, Philippines, spatial consequence